PENGEMBANGAN BUKU SAKU DIGITAL SEBAGAI MEDIA BIMBINGAN DAN KONSELING DALAM MENGELOLA KONFLIK ANTARPRIBADI SISWA SMK - Ramadhan Aulia Putri; Mahdum; Kiki Mariah (STKIP Subang, 2026)
This study was motivated by the high incidence of interpersonal conflicts among Vocational High School (VHS) students, which negatively affect their social relationships and learning concentration. The purpose of this study was to develop a digital pocketbook as a guidance and counseling medium to assist vocational high school students in managing interpersonal conflicts. This research employed the Research and Development (R&D) method using the ADDIE development model, which consists of the Analysis, Design, Development, and Implementation stages. The research subjects included media experts, material experts, vocational high school students, and guidance and counseling teachers. Data were collected through interviews, questionnaires, validation sheets, and practicality assessment instruments. The findings revealed that the developed digital pocketbook achieved a very high validity level, with an average percentage score of 98.05%. The practicality test results also indicated that the media was highly practical, with percentages of 90.00% from students and 95.55% from guidance and counseling teachers. The digital pocketbook was developed using the Heyzine Flipbook platform and was equipped with interactive features such as quizzes, self-reflection activities, and conflict management tips. Therefore, the developed digital pocketbook is considered suitable for use as a supporting medium in guidance and counseling services to enhance students’ understanding and skills in effectively managing interpersonal conflicts.